Comparison of Patiromer to Sodium Polystyrene Sulfonate in Acute Hyperkalemia. (June 2022) - Nguyen, Peter T.; Kataria, Vivek K.; Sam, Teena R.; Hooper, Katie; Mehta, Ankit N.
Background: Patiromer and sodium polystyrene sulfonate (SPS) are cation-exchangers approved for the treatment of chronic hyperkalemia. Data regarding their efficacy acutely is lacking. Despite this, both drugs are frequently used in the emergent setting.Objective: The purpose of this study was to compare the potassium reduction of patiromer to SPS within 6 to 24 hours following a single dose.Methods: This retrospective quality improvement project included hyperkalemic patients receiving 1 dose of patiromer or SPS and had a second potassium level drawn in 6 to 24 hours. Doses of 8.4 g of patiromer and 15 g of SPS were considered "low dose" while 16.8 g of patiromer and 30 g of SPS were considered "high dose." The presence of a dose-response relationship was assessed through a linear regression analysis.Results: Mean (SD) potassium reduction was higher in SPS than patiromer [0.76 (0.63) mEq/L vs 0.32 (0.65) mEq/L, ( P  = .001)]. A dose response relationship was not demonstrated in low versus high dose groups [−0.21 (0.14), P  = .13] and CKD, ESRD, and renal transplant patients when compared to patients with normal renal function [0.11 (0.17), P  = .51, −0.07 (0.19), P  = −0.07 (0.19), P  = .73, and −0.10 (0.22), P  = .65].Conclusions: This study suggests a clinically significant reduction in potassium with SPS compared to patiromer. Although SPS was successful in demonstrating this outcome, due to well-documented adverse reactions in the literature and a time to onset of 6 hours, it cannot be recommended for use in acute hyperkalemia either.